CCR9 signaling in dendritic cells drives the differentiation of Foxp3+ Tregs and suppresses the allergic IgE response in the gut. Issue 3 (1st December 2019) - Pathak, Manisha; Padghan, Priyanka; Halder, Namrita; Shilpi,; Kulkarni, Neeraja; Sonar, Sandip A.; Lal, Girdhari
Abstract: The chemokine receptor CCR9 and its only known ligand CCL25 play an important role in gut inflammation and autoimmune colitis. The function of CCR9‐CCL25 in the migration of immune cells is well characterized. However, its role in the immune cell differentiation is mostly not known. Using dextran sodium sulfate (DSS)‐induced gut inflammation model, we showed that CCR9 + dendritic cells (DCs) specifically CD11b − CD103 + DCs were significantly increased in the gut‐associated lymphoid tissues (GALT) compared to control mice. These CCR9 + DCs express lower MHC II and CD86 molecules and had regulatory surface markers (FasL and latency‐associated peptide, LAP) in the GALT. In the presence of CCL25, CCR9 + DCs promoted in vitro differentiation of Foxp3 + regulatory CD4 + T cells (Tregs). CCL25‐induced differentiation of Tregs was due to intrinsic signaling in the DCs but not through CD4 + T cells, which was driven by the production of thymic stromal lymphopoietin (TSLP) and not IL‐10. Furthermore, adoptive transfer of CCR9 + DCs in C57BL/6 mice promoted Tregs but reduced the Th17 cells in the GALT, and also suppressed the OVA‐specific gut‐allergic response. Our results suggest CCR9 + DCs have a regulatory function and may provide a new cellular therapeutic strategy to control gut inflammation and allergic immune reaction. Abstract : CCR9 + dendritic cells express higher FasL and latency‐associated peptide (LAP), and low MHC II and CD86 molecules. In the presence of CCL25, CCR9 + DCs produce thymic stromal lymphopoietin (TSLP) and promote the differentiation of Tregs but inhibits Th17 response and also inhibit the IgE production in the gut.